2014
DOI: 10.1111/acel.12271
|View full text |Cite
|
Sign up to set email alerts
|

Associations between age and gray matter volume in anatomical brain networks in middle‐aged to older adults

Abstract: Aging is associated with cognitive decline, diminished brain function, regional brain atrophy, and disrupted structural and functional brain connectivity. Understanding brain networks in aging is essential, as brain function depends on large-scale distributed networks. Little is known of structural covariance networks to study inter-regional gray matter anatomical associations in aging. Here, we investigate anatomical brain networks based on structural covariance of gray matter volume among 370 middle-aged to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
134
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(146 citation statements)
references
References 47 publications
(113 reference statements)
11
134
1
Order By: Relevance
“…Therefore, we choose to set the number of independent components in our study to ten components. This number is consistent with previous studies of brain networks, in which eight to ten components are most often applied (Cole et al, 2010, Hafkemeijer et al, 2014). A standard threshold level of 0.5 was used to describe significance of individual voxels within a spatial map.…”
Section: Methodssupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, we choose to set the number of independent components in our study to ten components. This number is consistent with previous studies of brain networks, in which eight to ten components are most often applied (Cole et al, 2010, Hafkemeijer et al, 2014). A standard threshold level of 0.5 was used to describe significance of individual voxels within a spatial map.…”
Section: Methodssupporting
confidence: 92%
“…This statistical technique with independent component analysis (ICA) defines fully automated spatial component maps of maximal statistical independence, which is commonly used to study functional network integrity. When applied on structural grey matter images, this method defines spatial components based on the co-variation of grey matter patterns among all participants (Hafkemeijer et al, 2014, Segall et al, 2012, Xu et al, 2009). Then, ICA provides for each participant a score (‘network integrity score’), which can be negative or positive, describing the strength of the individual expression in each network (Beckmann and Smith, 2004, Segall et al, 2012), with high scores indicating strong individual expression of the identified network.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, structural network architecture is known to mature across the lifespan (DuPre and Spreng 2017), including during both early childhood (Geng et al 2017) and late adulthood (Hafkemeijer et al 2014). Our focused age-range prohibits us from conclusively ascertaining the specificity of these changes to adolescence.…”
Section: Discussionmentioning
confidence: 99%